Shear Strength of Headed Stud Connectors in Self-Compacting Concrete with Recycled Coarse Aggregate - Samoel Mahdi Saleh; Fareed Hameed Majeed (Buildings, 2022)
This study investigated the use of self-compacting concrete (SCC) made with recycled coarse aggregates (RCAs), which represents a trend of producing environment-friendly concrete, integrated with hot-rolled steel sections by means of headed stud shear connectors in composite structures. Therefore, thirty-six push-out test specimens were examined to assess the shear strength and behavior of the headed stud connectors embedded in RCA-SCC, with the concrete compressive strength, stud diameter, and RCA ratio as the main variables. Four ratios of RCAs ranging from 0 to 60% were used to produce concrete with three different compressive strengths (25, 33, and 40 MPa) for each one. It was found that the use of SCC with RCAs had a negative effect on the shear strength of headed stud connectors. This negative effect could be reduced by increasing the concrete compressive strength and/or the stud diameter. Similarly, a reduction in the shear stiffness of the tested specimens was inversely proportional to the RCA ratio, while the ultimate slip was directly proportional to the RCA ratio. An evaluation of the test results was made by comparing them with those determined by Eurocode 4 and AASHTO LRFD.